Implementation of Red Ocean Strategy in MSMEs: A Case Study of Warung Sambal Nagih Bang Hepi Yogyakarta – Performance and Marketing Strategy Analysis - Zainul Muttaqin; Anas Hidayat; Zaenal Arifin (International Journal of Economics, Business and Innovation Research, 2025)
In starting a business, especially on the MSME (Micro, Small and Medium Enterprises) scale, many business people go directly into existing markets and existing business models or commonly called Red Ocean. Especially in the culinary business, if there are still humans alive, the need for food remains, the potential for the culinary business also remains. The application of the Red Ocean Strayegy theory in building the Warung Sambal Nagih Bang Hepi MSME business in Yogyakarta is a way for business people that entering into an existing market still has the potential to compete, but it is necessary to make adjustments to the added value of their business as an additional strategy. This research analyzes business performance from the aspects of marketing, production, human resources, and finance. The results showed that the implementation of Red Ocean Strategy with added values such as affordable prices, extra rice portions, and free delivery services succeeded in making the business survive in a competitive market. Solutions implemented include special promos, CRM management, and adaptation to national economic dynamics. The conclusion shows that the business still exists and survives with a surplus profit of IDR 4,695,500 in period January-October 2024.